Pemupukan Pada Tanaman Kakao ( Theobroma Cacao L) di Kelompok Tani Plea Puli Desa Bloro Kecamatan Nita - Brokarda Enjelin Kotten; Julianus Jeksen; Mario Malado (Institut Nalanda, 2023)
Cocoa is one of the main plantationcommodities in bloro village, especilly for the plea puli farmer group, Nita sub- district, sikka district. Cocoa plants ( Theobroma cacao L) are one of the leading exportcommodities with considerable potential in Indonesia. Cocoa plants occupy the third largest posiion in providing foreign exchange for the country in the plantation sub- sector, so it is necessary to increase the growth of cocoa plants byincreasing nutriens.the way to increase the nutrients of cocoa plants is by applying fertilizer during the vegetative and generative periods of the plants. The aim of this fertilization activity is tohelp the growth of roots,stems, flowers and fruit.This fertilization also pays attention to the fertilizer used and what is the right dose of fertilizer to apply to the cocoa plants